An evaluation of an aptamer for use as an affinity reagent with MS: PCSK9 as an example protein. (August 2016) - Gupta, Vinita; Lassman, Michael E; McAvoy, Thomas; Lee, Anita YH; Chappell, Derek L; Laterza, Omar F
Background: For quantitative immunoaffinity IA-LC–MS, the utility of antibodies has been demonstrated many times but the utility of aptamers as affinity reagents is unproven.Methods: Immunoaffinity reagents including a monoclonal antibody and an aptamer were coupled to magnetic beads and used as part of an enrichment strategy for PCSK9 quantitation in plasma.Results: With limited method development, we have established a comparison of an anti-PCSK9 aptamer with an anti-PCSK9 monoclonal antibody. The background that results from a tryptic digest of affinity enrichment in plasma was demonstrated for each reagent using high-resolution full scan MS. The assay recovery was demonstrated for multiple concentrations of aptamer in plasma with different concentrations of PCSK9 protein.Conclusion: The aptamer achieved comparable enrichment to the antibody, but with lower peptide background, thus demonstrating the potential use of aptamers for IA-LC–MS.